POLA ASUH ORANG TUA PENGRAJIN BATU BATA MERAH DALAM MENDIDIK SIKAP TANGGUNG JAWAB ANAK DI DESA KALIPUCANG WELAHAN JEPARA - Felia Tantri (IKIP Siliwangi, 2022)
The purpose of this study is to describe the attitude of children's responsibility in social life in Kalipucang Welahan Village, Jepara. This research uses descriptive qualitative research with case study method. Parenting style is parenting style of parents in carrying out their role as caregivers, educators, and companions for their children. There are three types of parenting styles, namely democratic, permissive, and authoritarian. Responsibility is the attitude that individuals have to carry out their obligations and are ready to face all the consequences for their words and actions. The subjects of this study were limited to four elementary school children aged 8-10 years in the development of this attitude of responsibility. Data collection techniques and instruments used in this study were observation, interviews and documentation. This study uses qualitative data analysis with reference to the concept of Miles and Huberman. The results of this study indicate that parenting applied by parents to children causes the development of children's attitudes of responsibility that are different from one another. There is one child who gets an authoritarian parenting pattern resulting in the child's attitude of responsibility is still low. One child gets democratic parenting so that the child has good responsibilities and can solve his own problems. Two children received permissive parenting which caused the children to have a fairly good attitude of responsibility.